Polymorphism of the maternal EGF gene is associated with the fetal growth retardation: a prospective comparative study - Oleg V. Golovchenko; Irina V. Ponomarenko; Mikhail I. Churnosov (IP Berlin A.V., 2021)
Aim. To study the involvement of polymorphism of growth factor genes and their receptors in the formation of fetal growth retardation (FGR). Materials and methods. In this prospective comparative study, genetic analysis of five polymorphic loci of growth factor genes and their receptors (rs4444903 EGF, rs833061 VEGFA, rs2981582 FGFR2, rs6214 IGF1, rs1800469 TGF1) was performed in 196 pregnant women with FGR and 324 pregnant women in the control group. For genotyping single-nucleotide polymorphism, the polymerase chain reaction method was used. The biomedical mechanisms underlying the identified associations were evaluated using modern bioinformatic resources: GTExportal (effect on gene transcription) and HaploReg (regulatory potential). Results. The allelic variant G rs4444903 of the EGF gene determines an increased risk of FGR in the following genetic models: allelic (OR 1.28, 95% CI 1.001.65; рperm=0.033), additive (OR 1.33, 95% CI 1.021.75; рperm=0.039) and dominant (OR 1.62, 95% CI 1.062.47; рperm=0.031). The polymorphism rs4444903 of the EGF gene has a significant epigenetic potential (in the field of promoters, enhancers, "open chromatin", transcription regulatory proteins), determines the expression of the EGF and GAR1 genes and alternative splicing of the GAR1 gene in organs and tissues (placenta, fetal and adult brain, etc.), which are significant for the pathophysiology of FGR. Conclusion. The associations rs4444903 of the EGF gene with the FGR are shown.